Poros Maritim dan Politik Luar Negeri Jokowi - Ali Maksum (Andalas Journal of International Studies (AJIS), 2015)
This article discusses the President Joko Widodo’s poros maritim dunia or global maritime axis and the Indonesian foreign policy. This policy optimistically to strengthen Indonesia’s maritime capability and also to reviving the country as maritime super power as in the early history. Once Joko Widodo seizes the mandate after his dramatic victory in the last presidential election 2014, political polarization becomes a serious challenge to his administration. Yet, at the same time he obtained a huge international attention. Thus, this article attempt to understand Joko Widodo’s maritime policy from foreign policy perspective. Basically, foreign policy is determined by two factors namely international and domestic. To be more systematic, this article divided into five sections i.e.; introduction, maritime axis and Jokowi’s foreign policy, maritime axis and domestic politics, maritime axis and neighboring countries, and conclusion